A kind of waterborne epoxy emulsified asphalt coating and preparation method thereof
Through the preparation method of water-based epoxy emulsified asphalt coating, combined with emulsified asphalt, water-based epoxy resin, modified talc powder and zinc phosphate, the shortcomings of traditional emulsified asphalt coatings in terms of aging resistance, waterproofness and corrosion resistance are solved. , significantly improves the strength, adhesion and corrosion resistance of the paint, and improves the overall performance.
Patent Information
- Application Number
- CN202310326266.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-30
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-03-30
AI Technical Summary
Traditional emulsified asphalt coatings have shortcomings in their aging resistance, waterproofness and corrosion resistance, and their low bonding, poor flexibility and insufficient strength, limiting their wide application in the field of building waterproofing.
Using the preparation method of aqueous epoxy emulsified bitumen coating, the emulsified bitumen and aqueous epoxy resin, modified talc powder, zinc phosphate and other components are combined to form components A and B, and the specific stirring and curing process is carried out. , improve the adhesive properties and corrosion resistance of the paint.
It significantly improves the strength, adhesion and corrosion resistance of the coating, improves rheology, elongation and oxidation resistance, thereby improving the overall performance of water-based epoxy bitumen coatings.
Smart Images

Figure BDA0004153322020000041 
Figure BDA0004153322020000042 
Figure BDA0004153322020000052
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of asphalt coatings, and in particular relates to a water-based epoxy emulsified asphalt coating and a preparation method thereof. Background Art
[0002] In engineering, petroleum asphalt is widely used in roofs, floors, bridge decks and other buildings because of its good anti-aging, waterproof and anti-corrosion properties. Traditional waterproof materials have shortcomings such as poor aging resistance and temperature sensitivity, which can easily cause aging, deformation, cracking and other phenomena on the building surface. The resulting building leakage has seriously affected daily life and industrial production. Emulsified asphalt coating has good impermeability, excellent anti-corrosion, crack resistance and temperature change resistance, thus becoming one of the methods to solve the problem of building waterproofing.
[0003] However, the disadvantages of single emulsified asphalt such as low adhesion, poor flexibility and insufficient strength have restricted the promotion and application of emulsified asphalt. How to improve the performance of emulsified asphalt means that the emulsified asphalt needs to be modified to have better adhesion, superior elastic recovery ability and good strength performance, etc. At present, there have been studies on modifying emulsified asphalt by using water-based epoxy resin emulsion and curing agent. The modified emulsified asphalt has good adhesion and high strength. However, actual application found that the flexibility and elongation of water-based annular emulsified asphalt are not good. In addition, in order to expand the application scope of emulsified asphalt, emulsified asphalt is also required to have good anti-corrosion properties. Therefore, higher requirements are put forward for the improvement of the overall performance of emulsified asphalt. Summary of the invention
[0004] In order to solve the above problems, the primary purpose of the present invention is to provide a water-based epoxy emulsified asphalt coating and a preparation method thereof.
[0005] The specific technical solutions of the present invention include:
[0006] The present invention provides a waterborne epoxy emulsified asphalt coating, wherein the waterborne epoxy emulsified asphalt coating comprises components in parts by weight:
[0007] Component A: 50-60 parts of emulsified asphalt, 20-30 parts of water-based epoxy resin, 0.15-0.25 parts of defoamer, 3-4 parts of film-forming aid, 0.6-0.8 parts of pH adjuster;
[0008] Component B: 5-10 parts of curing agent, 0.3-0.5 parts of dispersant, 4-5 parts of modified talc, 9-10 parts of zinc phosphate, and 0.15-0.25 parts of defoaming agent.
[0009] As a further optimization scheme of the present invention, the weight ratio of component A to component B is 20-30:1.
[0010] As a further optimization scheme of the present invention, the modified talc powder is obtained by adding talc powder to an o-methoxyphenol ethanol solution, stirring at 95° C. for 30 minutes, filtering and drying.
[0011] As a further optimization scheme of the present invention, the weight ratio of o-methoxyphenol to talc is 2-3:1.
[0012] As a further optimization scheme of the present invention, the solid content of the emulsified asphalt is between 40% and 65%, and the emulsified asphalt is one of cationic emulsified asphalt and anionic emulsified asphalt.
[0013] The present invention also provides a method for preparing the waterborne epoxy emulsified asphalt coating as described above, the steps of which include:
[0014] (1) Weigh the materials according to the components and proportions of waterborne epoxy emulsified asphalt coating;
[0015] (2) According to the components and proportions of the waterborne epoxy emulsified asphalt coating, water, defoamer and film-forming aid were first added to the reaction kettle and stirred at a low speed for 10 minutes, then the waterborne epoxy resin was added and stirred for 10 minutes, and then the pH regulator was added to adjust the system to a weak alkaline state. Finally, the emulsified asphalt was added and stirred for 30 minutes to obtain component A;
[0016] (3) According to the components and proportions of the waterborne epoxy emulsified asphalt coating, dispersant, defoamer, modified talcum powder, and zinc phosphate were added to another reaction kettle, stirred at a low speed for 10 minutes, and finally a curing agent was added and stirred for 20 minutes to obtain component B;
[0017] (4) Component A and component B are mixed evenly to obtain the water-based epoxy emulsified asphalt coating.
[0018] In summary, the beneficial effects of the present invention are:
[0019] The waterborne epoxy asphalt coating of the present invention has excellent performance. The addition of modified talcum powder and zinc phosphate can significantly improve the strength and adhesion of the coating, improve its rheological properties, and enhance the corrosion resistance of the coating. In addition, compared with the surface modification of traditional coupling agents, the surface modification of talcum powder modified with o-methoxyphenol can improve the oxidation resistance of the modified talcum powder and the elongation and adhesion of the coating as one of the coating components, thereby further improving the performance of the waterborne epoxy asphalt coating. DETAILED DESCRIPTION
[0020] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.
[0021] 1. Materials and Methods
[0022] The methods used in this example are conventional methods known to those skilled in the art unless otherwise specified, and the reagents and other materials used are commercially available products unless otherwise specified. Among them, the defoamer was purchased from Hefei Yueguan New Materials, model DE-Z001; the film-forming aid was purchased from Waidian International Chemical, model Fexanol 1951 water-based film-forming aid; the pH adjuster was purchased from Guangzhou Runhong Chemical, model AMP95; the curing agent was American Hansen Momentive, water-based epoxy curing agent EP1KURE 8545; the dispersant was purchased from Evonik Chemical, model SURFYNOL CT-171.
[0023] Example 1
[0024] This embodiment provides a method for preparing a waterborne epoxy emulsified asphalt coating, the steps comprising:
[0025] Weigh component A: 50 parts of emulsified asphalt, 30 parts of waterborne epoxy resin, 0.2 parts of defoamer, 3 parts of film-forming aid, 0.6 parts of pH adjuster; component B: 5 parts of curing agent, 0.3 parts of dispersant, 4 parts of modified talcum powder, 9 parts of zinc phosphate, 0.2 parts of defoamer. First add appropriate amount of water, 0.2 parts of defoamer and 3 parts of film-forming aid to the reactor and stir at low speed for 10 minutes. After adding 30 parts of waterborne epoxy resin and stirring for 10 minutes, add 0.6 parts of pH adjuster to adjust the system to weak alkalinity, add 50 parts of emulsified asphalt and stir for 30 minutes to obtain component A; add 0.3 parts of dispersant, 0.2 parts of defoamer, 4 parts of modified talcum powder, 9 parts of zinc phosphate to another reactor, stir at low speed for 10 minutes, add 5 parts of curing agent and stir for 20 minutes to obtain component B; mix components A and B to obtain the finished coating.
[0026] The modified talc is prepared by adding talc to an o-methoxyphenol ethanol solution, stirring at 95° C. for 30 minutes, filtering and drying, and the weight ratio of o-methoxyphenol to talc is 2:1.
[0027] The weight ratio between component A and component B is 20:1.
[0028] Example 2
[0029] This embodiment provides a method for preparing a waterborne epoxy emulsified asphalt coating, the steps comprising:
[0030] Weigh component A: 60 parts of emulsified asphalt, 20 parts of waterborne epoxy resin, 0.2 parts of defoamer, 3 parts of film-forming aid, 0.7 parts of pH adjuster; component B: 10 parts of curing agent, 0.4 parts of dispersant, 5 parts of modified talcum powder, 10 parts of zinc phosphate, and 0.2 parts of defoamer. First add appropriate amount of water, 0.2 parts of defoamer and 3 parts of film-forming aid to the reactor and stir at low speed for 10 minutes. After adding 20 parts of waterborne epoxy resin and stirring for 10 minutes, add 0.7 parts of pH adjuster to adjust the system to weak alkalinity, add 60 parts of emulsified asphalt and stir for 30 minutes to obtain component A; add 0.4 parts of dispersant, 0.2 parts of defoamer, 5 parts of modified talcum powder, and 10 parts of zinc phosphate to another reactor, stir at low speed for 10 minutes, add 10 parts of curing agent and stir for 20 minutes to obtain component B; mix components A and B to obtain the finished coating.
[0031] The modified talc is prepared by adding talc to an o-methoxyphenol ethanol solution, stirring at 95° C. for 30 minutes, filtering and drying, and the weight ratio of o-methoxyphenol to talc is 2:1.
[0032] The weight ratio between component A and component B is 20:1.
[0033] Example 3
[0034] This embodiment provides a method for preparing a waterborne epoxy emulsified asphalt coating, the steps comprising:
[0035] Weigh component A: 60 parts of emulsified asphalt, 20 parts of waterborne epoxy resin, 0.2 parts of defoamer, 3 parts of film-forming aid, 0.7 parts of pH adjuster; component B: 10 parts of curing agent, 0.4 parts of dispersant, 5 parts of modified talcum powder, 10 parts of zinc phosphate, and 0.2 parts of defoamer. First add appropriate amount of water, 0.2 parts of defoamer and 3 parts of film-forming aid to the reactor and stir at low speed for 10 minutes. After adding 20 parts of waterborne epoxy resin and stirring for 10 minutes, add 0.7 parts of pH adjuster to adjust the system to weak alkalinity, add 60 parts of emulsified asphalt and stir for 30 minutes to obtain component A; add 0.4 parts of dispersant, 0.2 parts of defoamer, 5 parts of modified talcum powder, and 10 parts of zinc phosphate to another reactor, stir at low speed for 10 minutes, add 10 parts of curing agent and stir for 20 minutes to obtain component B; mix components A and B to obtain the finished coating.
[0036] The modified talc is prepared by adding talc to an o-methoxyphenol ethanol solution, stirring at 95° C. for 30 minutes, filtering and drying, and the weight ratio of o-methoxyphenol to talc is 2:1.
[0037] The weight ratio between component A and component B is 30:1.
[0038] 2. Verification Test
[0039] 1. In order to explore the effect of talcum powder modification on the performance of coatings, the coatings were prepared according to the formula shown in Table 1.
[0040] Table 1. Coating composition formula
[0041]
[0042] 2. In order to explore the effect of talcum powder modification on the weight ratio of components A and B, the coating was prepared according to the formula shown in Table 2.
[0043] Table 2. Coating component formula
[0044]
[0045]
[0046] 3. Testing process
[0047] 3.1. Preparation of coating test pieces
[0048] The coatings prepared in each group were used to prepare coating test pieces. The polished iron sheets were dipped into the above coatings in turn by dipping method. Ten test pieces were prepared for each coating and labeled in turn. The test pieces were hung in an oven with the temperature set at 50°C to accelerate the drying speed of the paint film.
[0049] 3.2 Testing process
[0050] For the prepared samples, the QCJ impactor was used to measure the impact resistance of the paint film, the QTX paint film elasticity tester was used to measure the elasticity and flexibility of the paint film, the QHZ coating scratch tester was used to measure the strength and hardness of the paint film, and the QFH cross-cut adhesion tester was used to measure the adhesion of the paint film (standard GB / T 1720-1979).
[0051] The prepared coating test piece was immersed in the simulated seawater prepared in advance for corrosion test, and the temperature was increased in a water bath to accelerate corrosion. The corrosion condition of the coating test piece was observed and recorded every 5, 15 and 30 days.
[0052] 4. Results and Analysis
[0053] The impact resistance test results are shown in Table 3, the paint film elasticity and flexibility test results are shown in Table 4, the paint film strength test results are shown in Table 5, and the paint film corrosion resistance test results are shown in Table 6.
[0054] Table 3. Impact test results
[0055]
[0056]
[0057] It can be seen from Table 3 that the paint films prepared by the different formulations disclosed in Examples 1-3 all have good impact resistance test results, while the unmodified talcum powder used in Test Example 1 instead of the modified talcum powder in Examples 1-3 has a negative effect on the paint film of the paint, and the impact resistance test effect is significantly reduced. It can be seen that the surface modification of talcum powder can effectively improve the impact resistance of the paint film;
[0058] In addition, it can be seen from Test Examples 2-3 that the present application can achieve better results by using o-methoxyphenol than by using conventional silane coupling agents and aluminate coupling agents to modify talc. It can be seen from Test Example 4 that when the weight ratio of o-methoxyphenol to talc is 3:1, better results can also be achieved.
[0059] In addition, it can be seen from Comparative Examples 2-4 that by increasing the weight ratio of component B, Comparative Example 4 can achieve relatively better results compared to Experimental Example 2, but the overall effect is not as good as Examples 1-4.
[0060] Table 4. Test results of film elasticity and flexibility
[0061]
[0062] It can be seen from Table 4 that the paint films prepared by the different formulations disclosed in Examples 1-3 all have good elasticity and flexibility, while Test Example 1 uses unmodified talc instead of the modified talc in Examples 1-3. From the results, it can be seen that the paint film elasticity and flexibility of the paint are negatively affected. In addition, it can be seen from Test Example 4 that when the weight ratio of o-methoxyphenol to talc is 3:1, the effect is reduced compared with Examples 1-3. It can be seen that the increase in the amount of o-methoxyphenol will affect the elasticity and flexibility of the paint film. However, it can be seen from Comparative Example 5 that compared with Examples 1-3, when the weight ratio of component B is increased, the paint film can also achieve good elasticity and flexibility.
[0063] Table 5. Paint film strength and adhesion test results
[0064]
[0065] It can be seen from Table 5 that the paint films prepared with the different formulations disclosed in Examples 1-3 all have good strength and adhesion. When the weight ratio of o-methoxyphenol to talc is 3:1, the effect is reduced compared with Examples 1-3. It can be seen that an increase in the amount of o-methoxyphenol will affect the strength and adhesion of the paint film. It can be seen from Comparative Example 5 that even if the weight ratio of component B is increased, the strength and adhesion of the paint film are difficult to improve.
[0066] Table 6. Corrosion test results of paint films
[0067]
[0068]
[0069] Note: a represents the discoloration; the numbers 0, 1, 2, and 3 represent none, slight, moderate, and severe;
[0070] b is the blistering condition; the subscript numbers 0, 1, 2, and 3 represent none, slight, moderate, and severe;
[0071] c is the shedding situation; the subscript numbers 0, 1, 2, and 3 represent none, slight, moderate, and severe.
[0072] It can be seen from Table 6 that the paint films prepared by the different formulations disclosed in Examples 1-3 all have good anti-corrosion properties. However, in Example 4, the increase in the amount of o-methoxyphenol will affect the strength and adhesion of the paint film. Therefore, compared with Examples 1-3, its anti-corrosion performance is reduced, especially in the shedding of the paint film. It can be seen from Comparative Example 5 that by increasing the weight ratio of component B, the anti-corrosion performance of the paint film is improved compared with Examples 1-3.
[0073] Conclusion
[0074] The waterborne epoxy asphalt coating of the present invention has excellent performance. The addition of modified talcum powder and zinc phosphate can significantly improve the strength and adhesion of the coating, improve its rheological properties, and enhance the corrosion resistance of the coating. In addition, compared with the surface modification of traditional coupling agents, the surface modification of talcum powder modified with o-methoxyphenol can improve the oxidation resistance of the modified talcum powder and the elongation and adhesion of the coating as one of the coating components, thereby further improving the performance of the waterborne epoxy asphalt coating.
[0075] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A waterborne epoxy emulsified asphalt coating, characterized in that: The components by weight of the waterborne epoxy emulsified asphalt coating include: Component A: 50-60 parts of emulsified asphalt, 20-30 parts of waterborne epoxy resin, 0.15-0.25 parts of defoaming agent, 3-4 parts of film-forming aid, 0.6-0.8 parts of pH adjuster, wherein the solid content of the emulsified asphalt is between 40% and 65%, and the emulsified asphalt is one of cationic emulsified asphalt and anionic emulsified asphalt; Component B: 5-10 parts of curing agent, 0.3-0.5 parts of dispersant, 4-5 parts of modified talc, 9-10 parts of zinc phosphate, 0.15-0.25 parts of defoaming agent; The weight ratio of component A to component B is 20-30:
1. The modification method of the modified talcum powder is to add talcum powder to an o-methoxyphenol ethanol solution, stir at 95° C. for 30 minutes, filter and dry to obtain the modified talcum powder. The weight ratio of o-methoxyphenol to talcum powder is 2:
1.
2. A method for preparing a waterborne epoxy emulsified asphalt coating as claimed in claim 1, characterized in that: The steps include: (1) Weigh the materials according to the composition and proportion of waterborne epoxy emulsified asphalt coating; (2) According to the components and proportions of waterborne epoxy emulsified asphalt coating, first add water, defoamer and film-forming aid into the reaction kettle and stir at low speed for 10 minutes, then add waterborne epoxy resin and stir for 10 minutes, then add pH adjuster to adjust the system to weak alkalinity, and finally add emulsified asphalt and stir for 30 minutes to obtain component A; (3) According to the components and proportions of waterborne epoxy emulsified asphalt coating, dispersant, defoamer, modified talcum powder and zinc phosphate were added to another reactor respectively, stirred at low speed for 10 minutes, and finally, curing agent was added and stirred for 20 minutes to obtain component B; (4) Component A and component B are mixed evenly to obtain the water-based epoxy emulsified asphalt coating.
Citation Information
Patent Citations
Aqueous two-component epoxy asphalt coating and preparation method thereof
CN110551451A